2020
DOI: 10.1371/journal.pcbi.1007862
|View full text |Cite|
|
Sign up to set email alerts
|

Representation of foreseeable choice outcomes in orbitofrontal cortex triplet-wise interactions

Abstract: Shared neuronal variability has been shown to modulate cognitive processing. However, the relationship between shared variability and behavioral performance is heterogeneous and complex in frontal areas such as the orbitofrontal cortex (OFC). Mounting evidence shows that single-units in OFC encode a detailed cognitive map of task-space events, but the existence of a robust neuronal ensemble coding for the predictability of choice outcome is less established. Here, we hypothesize that the coding of foreseeable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…However, and somehow paradoxically, we observed that noise correlations were higher in trials where the animal made correct choices, suggesting that they may instead be useful for behavior [14] . Similar findings were also reported in other studies [99] , [79] .…”
Section: Computational Methods For Readout and Transmission Of Inform...supporting
confidence: 93%
See 1 more Smart Citation
“…However, and somehow paradoxically, we observed that noise correlations were higher in trials where the animal made correct choices, suggesting that they may instead be useful for behavior [14] . Similar findings were also reported in other studies [99] , [79] .…”
Section: Computational Methods For Readout and Transmission Of Inform...supporting
confidence: 93%
“…These methods are based on the idea of correlating the sensory information in neural activity (rather than just neural activity regardless of its information) with the behavioral outcome on a trial-to-trial basis. For example, a way to establish the relevance of a given neural feature for behavior consists in evaluating whether higher values of information in the neural feature correlate on a trial-by-trial basis with more accurate behavioral performance [105] , [106] , [99] . A rigorous information-theoretic way to quantify this intuition has been developed [9] using the concept of Intersection Information, which involves information between three variables, i.e.…”
Section: Intersecting Encoding and Readout To Understand Their Overal...mentioning
confidence: 99%
“… 20 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 Such dynamic coding means that the task features encoded by individual neurons can vary across sample, delay, and choice epochs 35 , 48 ; hence neurons not classically selective for individual task features may transiently contribute to short-term memory encoding and maintenance. 49 , 50 , 51 , 52 These observations highlight a coding regime that extends beyond straightforward mapping between behavior and the task-selective firing of individual units in PFC.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it has been reported that the higher-order interactions encode stimulus information 43 , 51 (see also refs. 52 , 53 for a simulation study) and relate to animals cognitive functions such as expectation 54 , perceptual accuracy 55 , and prediction 56 . Thus, they potentially provide important clues on the architecture of cortical circuitries functioning in living systems.…”
Section: Introductionmentioning
confidence: 99%